Solution‐Processed Aluminum Nanogratings for Wire Grid Polarizers. Issue 14 (9th May 2018) - Kang, Juhoon; Yun, Hae‐Su; Jang, Hyun‐Ik; Kim, Junho; Park, Jae Hong; Lee, Jung‐Yong
Abstract: The wire grid polarizer (WGP) consisting of parallel metal nanogratings is an attractive alternative to conventional polarizers because it offers thin layer thickness, easy integration capability, and outstanding chemical and thermal stability. In this report, a facile solution process is proposed for fabricating Al WGPs. High‐aspect‐ratio Al nanostructures are formed in a 1D nanoimprinted template by electroless plating. Because of the geometrically irreversible deposition and wet etching processes on the nanotemplate, only the embedded Al nanogratings are retained. The solution‐processed Al nanostructured WGP with a line width of 60 nm and a height of 150 nm exhibits an average extinction ratio of 104 and transmittance of 52.3% in the visible wavelengths. Abstract : A novel solution process for fabricating an Al wire grid polarizer (WGP) is proposed . Utilizing the geometrical irreversibility of conformal electroless plating and isotropic etching, embedded Al nanogratings for the WGP can be formed in a nanoimprinted template. The resulting solution‐processed Al WGP achieves an average extinction ratio of 104 and transmittance of 52.3% in the visible wavelengths.